Cultural Identity of the Khambu Community of Nepal and its Transformation (Voice of History, 2025)
This study explores the shifting cultural identity of the Khambu community in Nepal, focusing on the nature, causes, and consequences of this change. The research highlights the risk of the Khambu identity fading and aims to understand both historical and current cultural practices. It examines how cultural identity has evolved, identifying key factors driving this shift. Using cultural identity theory, the study assesses the benefits and challenges of these transformations. A qualitative, interpretivist approach guides the research, prioritizing the lived experiences and perspectives of Khambu individuals. Ethnographic methods such as in-depth interviews, participant observation, and document analysis are employed to gather rich and meaningful data. By engaging directly with community members, cultural leaders, and practitioners, the study captures the nuanced expressions of identity and the tensions caused by change.The research interprets cultural shifts through a context-sensitive lens, considering both external forces, such as modernization, migration, and government policies, and internal factors like generational changes and evolving community values. It offers insights into how Khambu traditions are maintained, adapted, or abandoned over time. Finally, the study provides recommendations to help preserve and strengthen Khambu cultural identity in the face of rapid change. Through its findings, it contributes to a deeper understanding of cultural identity theory and the resilience of indigenous traditions in contemporary society.